Dose-response relationship between Life's Essential 8 score and COPD risk: the NHANES cohort study 2007–2018 - Qian Huang; Quan Yuan; Wenqiang Li; Xiaoyu He; Qian He; Zhiping Deng (Frontiers in Medicine)
ObjectiveThis study aims to discuss the dose-response relationship between the Life's Essential 8 (LE8) score and chronic obstructive pulmonary disease (COPD).MethodsWe screened data from the National Health and Nutrition Examination Survey (NHANES) database for the years 2007–2018. Logistics regression analysis and subgroup analysis were used to explore the relationship between cardiovascular health (CVH) and COPD based on the LE8 score. Additionally, restricted cubic spline (RCS) plots were drawn to visually display the dose-response relationship.ResultsA total of 12,517 participants were included, of which 835 had COPD. After multivariable adjustment, the LE8 score was found to be linearly and inversely associated with the risk of developing COPD. A similar relationship was observed in the scores for health behavior factors, whereas the relationship was weaker for health factors. The RCS plots visually demonstrated the aforementioned dose-response relationship. Moreover, subgroup analyses showed that this relationship remained robust across different groups.ConclusionLE8 scores are inversely and linearly associated with the risk of developing COPD. Higher LE8 scores can reduce the risk of developing COPD in individuals over 40 years old, especially concerning health behavior factors.